In vitro assessment of Prunus japonica seed extract on human spermatozoa hypermotility and intracellular alkalization. (19th May 2022) - Kim, Ji Hyun; Chae, Mee Ree; Wijerathne, Tharaka Darshana; Cooray, Akila Dushyantha; Kim, Chul Young; Lee, Sung Won; Lee, Kyu Pil
Abstract: Prunus japonica var. nakaii is used in traditional Korean medicine to treat various conditions; however, it has not been investigated for treating male infertility. In this study, we investigated the in vitro effects of the ethanolic extract of P. japonica seeds on human sperm motility and identified its mechanism of action. Eleven male volunteers were selected, and the effects of the extract on human spermatozoa were assessed through a computer‐assisted semen analysis. The P. japonica seed extract increased the percentage of total and progressive motility of spermatozoa. To understand the mechanism of action, we monitored intracellular alkalization using flow cytometry and obtained electrophysiological recordings of human voltage‐gated proton channels hHv1 that were overexpressed in HEK‐293 cells. The extract shifted the activation curves in a concentration‐dependent manner. Two major constituents of the extract, linoleic acid and oleic acid, exhibited proton channel activity. Our in vitro experiments suggested that P. japonica seed extract could be potentially used to rescue sperm motility in idiopathic infertility patients via pharmacological modulation of the proton channels during capacitation. Therefore, our results indicate the therapeutic potential of P. japonica seed extract for treating male infertility.